PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS X MIPA2 SMA BABUSSALAM PEKANBARU - Ade Nugraheni; Sakur '; Kartini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was classroom action research that aims to improve learning process and to increase the student’s abilities in problem solving with apply Problem Based Learning (PBL). The subject of the research is students of class X MIPA2 SMA Babussalam Pekanbaru in the first semester academic years 2015/2016. There are 21 students in the class, consist of 7 boys and 14 girls. The research are two cycles, each a cycle has four stages, that are planning, implementation, observation, and reflection. Each end of the cycle carried out tests of mathematical problem solving ability. Data collected through observation and tests of mathematical problem solving ability. Data analysis was performed with narrative descriptive analysis and descriptive statistical analysis. Results of this research showed that the teacher’s activities and students have are increasing at eah meeting. Most of students were excited and active in problem solving and find the concept independently. Student also have confident to express their opinion and doing presentation. The student’s abilities in problem solving was increas if the N-gain average of student’s abilities in problem solving at first cycle and second cycle more than zero. Based on the analysis of data student’s abilities in problem solving, obtained the N-gain average of student’s abilities in problem solving at first cycle is zero point fourty. It means the student’s abilities in problem solving was increasing with enough classification. At second cycle, the N-gain average of student’s abilities in problem solving is zero point fifty six. It means the student’s abilities in problem solving was increasing with enough classification. Results of this research shows that Problem Based Learning (PBL) can improve the learning process and increase the student’s abilities in problem solving.Keywords: Student’s abilities in problem solving, Problem Based Learning